Low-viscosity lubricating oil and preparation method thereof

By using modified titanium silicon particles and viscosity index improvers in lubricating oils, the lack of performance problems of traditional lubricating oils in friction and wear are solved, and the efficient lubrication and wear resistance of low-viscosity lubricating oils are achieved to form a lubricating film. Reduce metal surface roughness and significantly improve lubrication and wear resistance.

CN119264971AActive Publication Date: 2025-01-07广东南油石化有限公司
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411401490.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-07
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Traditional lubricants are difficult to meet the requirements of efficient lubrication and wear resistance under increasingly severe friction and wear conditions. Single nano lubricating additives have poor dispersion and are difficult to achieve efficient lubrication.

Method used

Using a low viscosity lubricating oil formula, including 74 to 86 parts of base oil, 9 to 11 parts of modified titanium silicon particles and 2 to 4 parts of viscosity index improver, nanotitanium silicon particles with smooth surface are prepared by tightly coupled vacuum induction furnace. The zinc sulfate is combined with imidazosin by solvothermal method to form modified titanium silicon particles with a three-dimensional pore structure, which improves dispersion and lubrication effect.

Benefits of technology

Significantly reduce friction resistance, improve the lubricating effect and wear resistance of lubricating oil, form a lubricating film, reduce metal surface roughness, enhance wear resistance, and achieve friction reduction performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005075400440000051
    Figure BDA0005075400440000051
Patent Text Reader

Abstract

The invention discloses low-viscosity lubricating oil and a preparation method thereof, and relates to the technical field of lubricating oil. Titanium dioxide is combined with sodium silicate in a spray form by utilizing a tight coupling vacuum induction smelting furnace to form spherical nano titanium-silicon particles with smooth surfaces, so that the effect of a rolling bearing is realized, the friction resistance is reduced, the lubricating effect and the wear resistance of lubricating oil are remarkably improved, and meanwhile, the lubricating oil can enter a friction surface to form a lubricating film; the metal surface roughness is reduced, and the wear resistance is further enhanced; zinc sulfate, imidazosin and titanium silicon particles are combined through a solvothermal method, zinc atoms and nitrogen atoms in imidazosin are coordinated to form a cage-shaped coordination compound with zinc as a fulcrum and imidazosin as a frame, the cage-shaped coordination compound has a three-dimensional pore channel structure, the dispersity of the material in lubricating oil is improved, agglomeration is reduced, and therefore the lubricating effect is indirectly improved; and meanwhile, the lubricating oil can continuously enter the contact surface of a friction pair to fill up pits on the abraded surface, so that the antifriction performance is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricating oils, in particular to a low-viscosity lubricating oil and a preparation method thereof. Background Art

[0002] The contact between the friction pairs of large-scale construction machinery will lead to inevitable friction and wear, resulting in serious energy consumption and material loss. According to statistics, one-third of the world's energy consumption is caused by friction and wear. The energy consumption caused by friction has become a huge challenge to achieve carbon neutrality. Therefore, in modern technology, reducing friction and wear is of great significance. Lubrication technology plays an irreplaceable role in improving the energy efficiency and service life of mechanical equipment.

[0003] Generally speaking, the essence of lubrication technology is the use of lubricants, and lubricating oils that are stable in different environments are the most commonly used lubricants. In recent years, traditional lubricating oils have been unable to meet the requirements of friction reduction and anti-wear performance of contact surfaces in relative motion under increasingly severe conditions. Finding high-performance lubricating oil additives has become an effective and reasonable way to improve lubricating oil performance. Nanomaterials have received widespread attention in the field of tribology due to their unique structure and properties as well as their environmentally friendly characteristics. Metal organic framework materials are a new type of porous material that has attracted research in the field of tribology due to their good stability and structural controllability. However, a single nano-lubricating additive usually has the limitation of poor dispersibility and difficulty in achieving efficient lubrication. Summary of the invention

[0004] The object of the present invention is to provide a low-viscosity lubricating oil and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a low-viscosity lubricating oil, which mainly comprises 74 to 86 parts of base oil, 9 to 11 parts of modified titanium silicon particles, and 2 to 4 parts of viscosity index improver by weight.

[0006] Furthermore, the base oil has a kinematic viscosity of 14 to 30 mm at 40°C. 2 / s, kinematic viscosity at 100℃ is 4~10mm 2 / s, viscosity index is 120-130. .

[0007] Furthermore, the modified titanium silicon particles are prepared from nano titanium silicon particles, zinc sulfate and imidazoline through a solvent thermal method.

[0008] Furthermore, the nano titanium silicon particles are prepared by melting and combining titanium dioxide with sodium silicate in a closely coupled vacuum induction furnace in a spray form.

[0009] Furthermore, the model of the viscosity index improver is Exxon PT8920.

[0010] Furthermore, a method for preparing a low-viscosity lubricating oil comprises the following preparation steps:

[0011] (1) 34 to 58 parts of sodium silicate are placed in a vacuum melting crucible, and 37 to 61 parts of titanium dioxide are melted to obtain a molten liquid, the crucible is placed in a furnace, and when the ambient temperature reaches a certain temperature, the molten liquid is atomized and sprayed to obtain nano titanium silicon particles;

[0012] (2) dispersing 4 to 8 parts of nano titanium silicon particles in 56 to 110 parts of methanol, adding 21 to 43 parts of zinc sulfate and 16 to 32 parts of imidazolin, ultrasonicating at 25° C. and 120 rpm for 20 to 40 min, then transferring to a high-pressure reactor, reacting at 120 to 140° C. for 10 to 24 h, cooling naturally to 25° C., centrifuging at 3000 r / min for 10 to 16 min in a centrifuge, washing with deionized water and ethanol alternately until the pH is 6 to 7, and drying in an oven at 50 to 60° C. for 12 to 16 h to obtain modified titanium silicon particles;

[0013] (3) 74-86 parts of base oil, 9-11 parts of modified titanium silicon particles, and 2-4 parts of Exxon PT8920 viscosity index improver are mixed uniformly to prepare a low-viscosity lubricating oil.

[0014] Furthermore, the vacuum degree of the vacuum melting crucible in step (1) is -0.06 to -0.08 MPa.

[0015] Furthermore, the certain temperature in step (1) is 550-650°C.

[0016] Furthermore, the atomization spraying conditions in step (1) are: atomization medium Ar gas, atomization pressure 2.5-4.5 MPa, atomization flow rate 21-33 m 3 / min.

[0017] Furthermore, the ultrasonic frequency in step (2) is 50 kHz.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The invention utilizes a tightly coupled vacuum induction furnace to melt titanium dioxide and sodium silicate in a spray form to form spherical nano titanium silicon particles with smooth surfaces, thereby achieving the effect of a rolling bearing, reducing friction resistance, significantly improving the lubricating effect and wear resistance of lubricating oil, and being able to enter the friction surface to form a lubricating film, thereby reducing the roughness of the metal surface and further enhancing the wear resistance. Then, zinc sulfate, imidazolin and titanium silicon particles are combined by a solvent thermal method, and zinc atoms are coordinated with nitrogen atoms in imidazolin to form a cage-like coordination compound with zinc as a fulcrum and imidazolin as a framework. The cage-like coordination compound has a three-dimensional pore structure, thereby improving the dispersibility of the material in the lubricating oil and reducing agglomeration, thereby indirectly improving the lubricating effect. At the same time, the energy can continuously enter the contact surface of the friction pair to fill the pits on the wear surface and achieve friction reduction performance. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the low-viscosity lubricating oil prepared in the following examples are as follows:

[0022] Kinematic viscosity at 40°C / 100°C: The same mass of the embodiment and the comparative example were tested according to ASTM D445.

[0023] CCS viscosity: the same mass of the embodiment and the comparative example were tested according to ASTM D5293.

[0024] Wear scar diameter: The same mass of the examples and comparative examples was taken and measured for 30 minutes under the conditions of 1800 rpm, 80° C. oil temperature and 30 kg load according to ASTM D4172. After the test, the test ball was removed, the wear scar was measured, and the wear scar was measured.

[0025] Example 1

[0026] (1) 34 parts of sodium silicate were placed in a vacuum melting crucible and the vacuum was reduced to -0.06 MPa. 37 parts of titanium dioxide were melted to obtain a molten liquid. The crucible was placed in a furnace. When the ambient temperature reached 550°C, the atomizing medium was Ar gas, the atomizing pressure was 2.5 MPa, and the atomizing flow rate was 21 m 3 / min, atomizing and spraying the melt to obtain nano titanium silicon particles;

[0027] (2) 4 parts of nano titanium silicon particles were dispersed in 56 parts of methanol, 21 parts of zinc sulfate and 16 parts of imidazolin were added, and ultrasonic treatment was performed at 25°C, 120 rpm and a frequency of 50 kHz for 20 min, and then transferred to a high-pressure reactor, reacted at 120°C for 10 h, naturally cooled to 25°C, placed in a centrifuge and centrifuged at 3000 r / min for 10 min, and washed alternately with deionized water and ethanol until the pH was 6, and dried in an oven at 50°C for 12 h to obtain modified titanium silicon particles;

[0028] (3) 74 parts of base oil, 9 parts of modified titanium silicon particles, and 2 parts of Exxon PT8920 viscosity index improver were mixed uniformly to prepare a low-viscosity lubricating oil.

[0029] Example 2

[0030] (1) 46 parts of sodium silicate were placed in a vacuum melting crucible and the vacuum was reduced to -0.07 MPa. 49 parts of titanium dioxide were melted to obtain a molten liquid. The crucible was placed in a furnace. When the ambient temperature reached 600°C, the atomizing medium was Ar gas, the atomizing pressure was 3.5 MPa, and the atomizing flow rate was 27 m 3 / min, atomizing and spraying the melt to obtain nano titanium silicon particles;

[0031] (2) 6 parts of nano titanium silicon particles were dispersed in 83 parts of methanol, 32 parts of zinc sulfate and 24 parts of imidazosin were added, and ultrasonic treatment was performed at 25°C, 120 rpm and a frequency of 50 kHz for 30 min, and then transferred to a high-pressure reactor, reacted at 130°C for 17 h, and naturally cooled to 25°C. The particles were centrifuged at 3000 r / min for 13 min, and washed alternately with deionized water and ethanol until the pH was 6.5, and dried in an oven at 55°C for 14 h to obtain modified titanium silicon particles;

[0032] (3) 80 parts of base oil, 10 parts of modified titanium silicon particles, and 3 parts of Exxon PT8920 viscosity index improver were mixed uniformly to prepare a low-viscosity lubricating oil.

[0033] Example 3

[0034] (1) 58 parts of sodium silicate were placed in a vacuum melting crucible and the vacuum was reduced to -0.08 MPa. 61 parts of titanium dioxide were melted to obtain a molten liquid. The crucible was placed in a furnace. When the ambient temperature reached 650°C, the atomizing medium was Ar gas, the atomizing pressure was 4.5 MPa, and the atomizing flow rate was 33 m 3 / min, atomizing and spraying the melt to obtain nano titanium silicon particles;

[0035] (2) 8 parts of nano titanium silicon particles were dispersed in 110 parts of methanol, 43 parts of zinc sulfate and 32 parts of imidazosin were added, and ultrasonic treatment was performed at 25°C, 120 rpm and a frequency of 50 kHz for 40 min, and then transferred to a high-pressure reactor, reacted at 140°C for 24 h, and naturally cooled to 25°C. The particles were centrifuged at 3000 r / min for 16 min, and washed alternately with deionized water and ethanol until the pH was 7, and dried in an oven at 60°C for 16 h to obtain modified titanium silicon particles;

[0036] (3) 86 parts of base oil, 11 parts of modified titanium silicon particles, and 4 parts of Exxon PT8920 viscosity index improver were mixed uniformly to prepare a low-viscosity lubricating oil.

[0037] Comparative Example 1

[0038] The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: 46 parts of sodium silicate and 49 parts of titanium dioxide are dispersed in 195 parts of water, transferred into a high-pressure reactor, reacted at 160° C. for 17 hours, naturally cooled to 25° C., placed in a centrifuge at 3000 r / min for 13 minutes, washed alternately with deionized water and ethanol until the pH is 6.5, and dried in an oven at 55° C. for 14 hours to obtain nano titanium silicon particles. The remaining steps are the same as those of Example 2.

[0039] Comparative Example 2

[0040] The difference between Comparative Example 2 and Example 2 is that there is no step (1), and step (2) is changed to: 6 parts of silicon dioxide are dispersed in 83 parts of methanol, 32 parts of zinc sulfate and 24 parts of imidazolin are added, and ultrasonication is performed at 25°C, 120rpm and a frequency of 50kHz for 30 minutes, then transferred to a high-pressure reactor, reacted at 130°C for 17 hours, naturally cooled to 25°C, placed in a centrifuge and centrifuged at 3000r / min for 13 minutes, washed alternately with deionized water and ethanol until the pH is 6.5, and dried in an oven at 55°C for 14 hours to obtain modified titanium silicon particles. The remaining steps are the same as those in Example 2.

[0041] Comparative Example 3

[0042] The difference between Comparative Example 3 and Example 2 is that there is no step (1), and step (2) is changed to: 6 parts of titanium dioxide are dispersed in 83 parts of methanol, 32 parts of zinc sulfate and 24 parts of imidazosin are added, and ultrasonication is performed at 25°C, 120rpm and a frequency of 50kHz for 30 minutes, then transferred to a high-pressure reactor, reacted at 130°C for 17 hours, naturally cooled to 25°C, placed in a centrifuge and centrifuged at 3000r / min for 13 minutes, washed alternately with deionized water and ethanol until the pH is 6.5, and dried in an oven at 55°C for 14 hours to obtain modified titanium silicon particles. The remaining steps are the same as those in Example 2.

[0043] Comparative Example 4

[0044] The difference between Comparative Example 4 and Example 2 is that there is no step (2), and step (3) is changed to: 80 parts of base oil and 3 parts of Exxon PT8920 viscosity index improver are mixed evenly to prepare low-viscosity lubricating oil. The remaining steps are the same as those in Example 2.

[0045] Effect example

[0046] Table 1 below shows the performance analysis results of the low-viscosity lubricating oils of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.

[0047] Table 1

[0048]

[0049] From the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 1, it can be found that titanium dioxide is melted and combined with sodium silicate in the form of a spray using a tightly coupled vacuum induction furnace to form spherical nano-titanium silicon particles with a smooth surface, thereby achieving the effect of a rolling bearing, reducing friction resistance, and significantly improving the lubricating effect and wear resistance of the lubricating oil; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 2, it can be found that titanium dioxide can enter the friction surface to form a lubricating film, reduce the roughness of the metal surface, and further enhance the wear resistance; from the comparison of the experimental data of Examples 1, 2, and 3 with those of Comparative Example 3, it can be found that sodium silicate is converted into silicon dioxide at high temperature, which plays the role of a rolling bearing, reducing friction resistance, and significantly improving the lubricating effect and wear resistance of the lubricating oil. Low friction resistance significantly improves the lubricating effect and wear resistance of the lubricating oil, and can enter the friction surface to form a lubricating film, reduce the roughness of the metal surface, and further enhance the wear resistance; from the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4, it can be found that zinc sulfate, imidazosin and titanium silicon particles are combined by a solvent thermal method, and the zinc atoms are coordinated with the nitrogen atoms in the imidazosin to form a cage-like coordination compound with zinc as the fulcrum and imidazosin as the framework, which has a three-dimensional pore structure, improves the dispersibility of the material in the lubricating oil, reduces agglomeration, and thus indirectly improves the lubrication effect. At the same time, it can continuously enter the contact surface of the friction pair to fill the pits on the wear surface and achieve friction reduction performance.

[0050] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A low viscosity lubricating oil, characterized in that: The low-viscosity lubricating oil mainly comprises 74-86 parts of base oil, 9-11 parts of modified titanium silicon particles, and 2-4 parts of viscosity index improver by weight.

2. A low-viscosity lubricating oil according to claim 1, characterized in that: The base oil has a kinematic viscosity of 14 to 30 mm at 40°C. 2 / s, kinematic viscosity at 100℃ is 4~10mm 2 / s, viscosity index is 120-130.

3. A low-viscosity lubricating oil according to claim 2, characterized in that: The modified titanium silicon particles are prepared from nano titanium silicon particles, zinc sulfate and imidazoline through a solvent thermal method.

4. A low-viscosity lubricating oil according to claim 3, characterized in that: The nano titanium silicon particles are prepared by melting and combining titanium dioxide with sodium silicate in a closely coupled vacuum induction furnace in a spray form.

5. A low-viscosity lubricating oil according to claim 1, characterized in that: The model of the viscosity index improver is Exxon PT8920.

6. A method for preparing a low-viscosity lubricating oil, characterized in that: The method comprises the following preparation steps: (1) 34 to 58 parts of sodium silicate are placed in a vacuum melting crucible, and 37 to 61 parts of titanium dioxide are melted to obtain a molten liquid, the crucible is placed in a furnace, and when the ambient temperature reaches a certain temperature, the molten liquid is atomized and sprayed to obtain nano titanium silicon particles; (2) dispersing 4 to 8 parts of nano titanium silicon particles in 56 to 110 parts of methanol, adding 21 to 43 parts of zinc sulfate and 16 to 32 parts of imidazolin, ultrasonicating at 25° C. and 120 rpm for 20 to 40 min, then transferring to a high-pressure reactor, reacting at 120 to 140° C. for 10 to 24 h, cooling naturally to 25° C., centrifuging at 3000 r / min for 10 to 16 min in a centrifuge, washing with deionized water and ethanol alternately until the pH is 6 to 7, and drying in an oven at 50 to 60° C. for 12 to 16 h to obtain modified titanium silicon particles; (3) 74-86 parts of base oil, 9-11 parts of modified titanium silicon particles, and 2-4 parts of Exxon PT8920 viscosity index improver are mixed uniformly to prepare a low-viscosity lubricating oil.

7. The method for preparing a low-viscosity lubricating oil according to claim 6, characterized in that: The vacuum degree of the vacuum melting crucible in step (1) is -0.06 to -0.08 MPa.

8. The method for preparing a low-viscosity lubricating oil according to claim 6, characterized in that: The certain temperature in step (1) is 550-650°C.

9. The method for preparing a low-viscosity lubricating oil according to claim 6, characterized in that: The atomization spraying conditions in step (1) are: atomization medium Ar gas, atomization pressure 2.5-4.5 MPa, atomization flow rate 21-33 m 3 / min.

10. The method for preparing a low-viscosity lubricating oil according to claim 6, characterized in that: The ultrasonic frequency in step (2) is 50 kHz.

Citation Information

Patent Citations

  • Methods of making superfine alloys

    CN101307399A

  • Lubricating oil for engineering machinery and preparation method thereof

    CN108795540A

  • High-strength wear-resistant skeleton oil seal for automobile bearings

    CN109535719A

  • Clean lubricating oil based on nano technology and production process thereof

    CN110157515A

  • Anti-wear additive, preparation method thereof and application of anti-wear additive in oil products

    CN115895752A